Cross-Country Herding Behavior in Chemical Industry Stocks: Evidence from Indonesia, Japan, and China Stock Markets - Veliana Felicia Santosa; Gusni (JURNAL MANAJEMEN MOTIVASI, 2026)
This study investigates herding behavior and cross-country herding dynamics in the chemical sector stock markets of Indonesia, China, and Japan using the Cross-Sectional Absolute Deviation (CSAD) approach. The results reveal heterogeneous herding patterns across countries. No significant herding behavior is observed in Indonesia, suggesting that investors generally make independent decisions. In contrast, Japan exhibits strong herding behavior, particularly during periods of market uncertainty, while China shows herding with lower intensity. Cross-country analysis further indicates that market movements and investor sentiment in one country affect other markets, highlighting the increasing integration and interdependence of global financial markets. Keywords: Herding Behavior; Cross-country Herding; Chemical Industry; CSAD